- DAMPAK LA NINA TERHADAP PENAMBAHAN CURAH HUJAN DAN TINGKAT RESIKO DI JAWA TENGAH - Abdullah, Sri Endah (Stasiun Pemantau Atmosfer Global Bukit Kototabang, 2024)
Central Java Province is one of the national food buffer provinces. One of the factors that influence the productivity of the agricultural and horticultural sectors is weather/climate conditions, including anomalies that cause weather/climate changes. Therefore, analysis and research related to weather/climate potential, especially regarding rainfall, needs to be updated to determine adaptation actions for farmers and related stakeholders. Rainfall as a climate element apart from its dynamic nature, the physical processes involved are also very complex. This rain uncertainty becomes greater when climate anomalies occur in the form of El Nino and La Nina. The influence of the La Nina phenomenon on increasing rainfall intensity is also possible in Central Java Province. Based on analysis of monthly rainfall data and monthly nino 3.4 index data for 30 years (1991-2020) using the frequency analysis method and bootstrapping method, the moderate to very high risk was concentrated in the SON period in most areas of Central Java with increasing rainfall (40 -70%). The impact of La NiÃ±a provides an increase in rainfall of up to >100% with a moderate to high risk of occurring during the JJA period in the West Coast to East Pantura areas of Central Java. Meanwhile, the DJF and MAM periods increased rainfall (20 â€“ 70%) but with low to very low risk in almost all areas of Central Java.